Collaborative Learning in Small Group Discussions and Its Impact on Resilience Quotient and Academic Performance - Estimo, Emeliza T.; Aranador, Lourdes C.; Evidente, Luis G. (JPAIR Multidisciplinary Research, 2012)
This paper is a quasi-experimental investigation on the impact of Collaborative Learning (CL) in Small Group Discussions (SGD) on the development of the eight components of Resilience Quotient (RQ) and the Academic Performance (AP) of students in Maritime English classes. Using different statistical tools such as mean and standard deviation and t-test for dependent and independent means, the study revealed that students who have a higher academic performance tend to also have a higher RQ. Evidence also showed that a high level of RQ could enhance academic performance and that RQ could be developed through constant exposure to small group discussions at a certain period of time. Evidence in the study also showed that too much dependence on the teacher as the main source of learning in the traditional approach could lead to some regression or decline on the students’ personal vision thereby lowering their level of resilience. There was also some evidence that the improvement in the level of RQ can also be a teacher factor. Moreover, it was noticed that working in small groups could give students the opportunity to affirm their personal beliefs and individual capabilities in accomplishing their tasks in the teaching and learning process.